2018
DOI: 10.3389/fnhum.2018.00075
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Accumbens and Thalamic White Matter Connectivity Revealed by Diffusion Tensor Tractography in Young Men with Genetic Risk for Obesity

Abstract: Background: Neurovascular coupling is associated with white matter (WM) structural integrity, and it is regulated by specific subtypes of dopaminergic receptors. An altered activity of such receptors, highly expressed in reward-related regions, has been reported in carriers of obesity-risk alleles of the fat mass and obesity associated (FTO) gene. Among the reward-related regions, the thalamus and the nucleus accumbens are particularly vulnerable to blood pressure dysregulation due to their peculiar anatomo-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Further, Wiemerslage's sample shows significant BMI differences and includes overweight participants, whereas Melhorn uses a matched sample of participants with average BMI. Thus, although the present findings are consistent with some of the existing literature, the use of mixed methodologies and exclusion of the cerebellum from analyses in nearly half of the existing literature 7,11,12 precludes studies from ascertaining what role, if any, the cerebellum plays in FTO‐ related risk for obesity. Of note, the four aforementioned studies documenting FTO differences all examined different FTO SNPs (rs1421085, rs17817449, and rs9939609).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Further, Wiemerslage's sample shows significant BMI differences and includes overweight participants, whereas Melhorn uses a matched sample of participants with average BMI. Thus, although the present findings are consistent with some of the existing literature, the use of mixed methodologies and exclusion of the cerebellum from analyses in nearly half of the existing literature 7,11,12 precludes studies from ascertaining what role, if any, the cerebellum plays in FTO‐ related risk for obesity. Of note, the four aforementioned studies documenting FTO differences all examined different FTO SNPs (rs1421085, rs17817449, and rs9939609).…”
Section: Discussionsupporting
confidence: 79%
“…Overall lower brain volumes, 5 as well as specific volumetric reductions in the nucleus accumbens, 6 have been documented in FTO risk allele carriers relative to noncarriers. Further, white matter (WM) microstructure abnormalities have been detected in risk allele carriers in the anterior thalamic radiations and the accumbofrontal fasciculus 7 . However, one study failed to document differences in WM integrity across genotypes 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Still, a wide range of behavioural symptoms, as those reported in KLS, seem to depend on the dopaminergic portion of the reward network. The ventral/limbic part of the network, including the anterior thalamic radiation, nucleus accumbens, caudate nucleus and the putamen, has been reported in connection with obesity, hypersexuality, aggressive behaviour and gambling [ 26 30 ]. In addition, the accumbo-frontal fasciculus and the anterior thalamic radiation are part of a cortico-striato-thalamo-cortical loop [ 29 ] which contain structures that also are targets for deep brain stimulation (DBS) in obsessive-compulsive and other psychiatric disorders [ 31 , 32 ].…”
Section: Recent Neuroimaging Findings In Klsmentioning
confidence: 99%
“…However, the observational nature of the study precludes definitive conclusions regarding the direction of the observed associations. Moreover, “third variable” causes such as genes that impact both BMI and limbic brain structure/function cannot be excluded 189‐191 …”
Section: Vascular‐related Neuroimagingmentioning
confidence: 99%